The Middling Citizenship Trap: Belonging Denied Through Neoliberal Exclusionary Inclusion in South Africa (African Human Mobility Review, 2025)
This ethnographic study examines 26 first-generation professional middle-class naturalized South African citizens, using purposive sampling from 2019 to 2022. These citizens experience racial violence and sociocultural exclusion despite legal inclusion. The research investigates “middling citizenship,” which has become a liminal space where naturalized professionals navigate between legal legitimacyand cultural foreignization in post-apartheid neoliberal governance. Despite state naturalization granting legal belonging, participants struggle with integration, as racialized boundaries sustain exclusion, while economic capital permits only partial inclusion. The findings show how naturalized citizens use their economic power to resist marginalization. They do this by performing belonging through economic visibility while remaining culturally invisible. The study unmasks the neoliberal paradox of middling citizenship, exposing post-apartheid contradictions. Rainbow Nation rhetoric promises colorblind integration, but in practice, it perpetuates colonial racial hierarchies. The results show that merit-based citizenship creates conditional belonging, privileging economic performance over cultural acceptance. Postcolonial frameworks are needed to acknowledge authentic belonging beyond economic legitimacy in transitional democracies.